2021
DOI: 10.3390/fractalfract5040149
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Dynamics of Typhoid Fever Transmission Models with Mass Vaccination Perspectives

Abstract: In this work, we formulate and mathematically study integer and fractional models of typhoid fever transmission dynamics. The models include vaccination as a control measure. After recalling some preliminary results for the integer model (determination of the epidemiological threshold denoted by Rc, asymptotic stability of the equilibrium point without disease whenever Rc<1, the existence of an equilibrium point with disease whenever Rc>1), we replace the integer derivative with the Caputo derivative. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In this selection process, we found that some articles did not contain the content that we were looking for. The references in [25][26][27][28] study typhoid disease using the fractional differential system to represent the transmission of the disease. Another article in [29] studies typhoid disease transmission by considering the spatial data factor in the model.…”
Section: The Prisma Methodsmentioning
confidence: 99%
“…In this selection process, we found that some articles did not contain the content that we were looking for. The references in [25][26][27][28] study typhoid disease using the fractional differential system to represent the transmission of the disease. Another article in [29] studies typhoid disease transmission by considering the spatial data factor in the model.…”
Section: The Prisma Methodsmentioning
confidence: 99%
“…The use of non-integer operators has emerged recently in the different disciplines of engineering and the physical sciences [35][36][37][38][39][40]. For instance, the fractional kinetic equation is important to investigate the theory of gases, aerodynamics, and astrophysics [41][42][43][44][45][46][47][48].…”
Section: Formulation Of Fractional Kinetic Equation Involving Riemann...mentioning
confidence: 99%
“…Modelling of epidemic diseases is of utmost importance to understand the behaviour of the ailment across time and to devise appropriate safeguards for the same. Numerous epidemic models have been developed for various diseases, including dengue and chikungunya [1], typhoid [2], cholera [10], HIV/AIDS [11], Covid-19 [14], [15], [57], leptospirosis, H1N1, measles [17], and others. But to our surprise there is not enough research on transmission dynamics and LSD control using a compartmental modelling technique; by the time this study was completed, there had only been one work [46], to examine the effects of vaccination on LSD and the spread of the illness in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%